Genetic and behavioral characterization of a Kmt2d mouse mutant, a new model for Kabuki Syndrome. (23rd April 2019) - Yamamoto, Pedro K.; de Souza, Tiago A.; Antiorio, Ana T. F. B.; Zanatto, Dennis A.; Garcia‐Gomes, Mariana de Souza A.; Alexandre‐Ribeiro, Sandra R.; Oliveira, Nicassia de Souza; Menck, Carlos F. M.; Bernardi, Maria M.; Massironi, Silvia M. G.; Mori, Claudia M. C.
Abstract : The recessive mutant mice bate palmas (bapa) ‐ claps in Portuguese arose from N‐ethyl‐N‐nitrosourea mutagenesis. A single nucleotide, T > C, change in exon 13, leading to a Thr1289 Ala substitution, was identified in the lysine (K)‐specific methyltransferase 2D gene ( Kmt2d ) located on chromosome 15. Mutations with a loss‐of‐function in the KMT2D gene on chromosome 12 in humans are responsible for Kabuki syndrome (KS). Phenotypic characterization of the bapa mutant was performed using a behavioral test battery to evaluate the parameters related to general activity, the sensory nervous system, the psychomotor system, and the autonomous nervous system, as well as to measure motor function and spatial memory. Relative to BALB/cJ mice, the bapa mutant showed sensory and psychomotor impairments, such as hypotonia denoted by a surface righting reflex impairment and hindquarter fall, and a reduction in the auricular reflex, suggesting hearing impairment. Additionally, the enhanced general activity showed by the increased rearing and grooming frequency, distance traveled and average speed possibly presupposes the presence of hyperactivity of bapa mice compared with the control group. A slight motor coordination dysfunction was showed in bapa mice, which had a longer crossing time on the balance beam compared with BALB/cJ controls. Male bapa mice also showed spatial gait pattern changes, such as a shorter stride length and shorter step length. In conclusion, the bapa mouse may be a valuable animal model to study the mechanisms involved in psychomotor and behavior impairments, such as hypotonia, fine motor coordination and hyperactivity linked to the Kmt2d mutation. Abstract : Comparison and filtering steps were performed to select only exclusive homozygous nonsynonymous or splice site variants in the bapa mutant compared with inbred strains as well as those in the Mouse Genomes Project database (REL‐1211) (A); Validation of the candidate single nucleotide variant (SNV) by Sanger sequencing of genomic DNA samples from bapa mutant (−/−) and C57BL/6J, BALB/cJ, A/J mice as well as an unrelated N‐ethyl‐N‐nitrosourea‐mutant controls (+/+) (B); SNV candidate found in exon 13 of Kmt2d gene, which creates a nonsynonym exchange of a threonine residue to an alanine residue in KMT2D protein (C).